Allelic divergence and heritable interrelationship studies for yield and submergence tolerance in rice (Oryza sativa L.) - Naveen-Kumar; Sakthivel, V; Premnath, A; Swaminathan, M; Alagarsamy, S; Manickam, S; Muthurajan, R (Plant Science Today, 2024)
Global low-lying rice cultivation faces a serious threat of flash floods, exacerbated by climate change. Significant progress has been made by plant breeders to introgress Sub1 locus into elite rice background through marker-assisted breeding approaches. The F2 population derived from the ADT 36 × #91-27 (NIL of CO 43 Sub1) was used to identify high-yielding lines that are homozygous for the Sub1 locus and Pi54 gene. INDEL markers, ART 5 and Pi 54, were used for genotyping the Sub1 locus and Pi54 gene, respectively. Out of 83 F2 plants, 21 plants are homozygotes and 45 plants are heterozygotes for the Sub1 locus. Whereas 21 plants are homozygotes and 46 are heterozygotes for the Pi54 gene. Four plants were identified to be homozygotes for the Sub1 locus and Pi54 gene. Genetic analysis of the F2 plants identified that productive tillers (number/plant) and the filled grains (number/panicle) exerted the highest positive effect on the single plant yield and also had the highest heritability. Also, these traits have a significant positive correlation per se. These traits, particularly productive tillers (number/plant), can potentially be used in subsequent generations to select high-yielding submergence tolerance and blast resistant lines of ADT 36 × #91-27 (NIL of CO 43 Sub1).